The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.nbd.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ induced nitric oxide mediates in vitro neuronal damage by Trypanosoma cruzi-infected macrophages

Abstract: Neuronal lesions and peripheral denervation in Chagas' disease are related to local inflammation; however, the pathogenic mechanisms of neuronal lesions in the heart and megavisceras are still unclear. We investigated the involvement of nitric oxide (NO) on neuronal lesion in co-cultures of neurons and macrophages. Trypanosoma cruzi-infected and interferon-gamma (IFN-gamma)-activated co-cultures of neurons and wild-type (WT) macrophages showed significant reduction of both neuronal survival and neurite density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
(64 reference statements)
1
19
0
2
Order By: Relevance
“…Of note, Arantes et al [63] reported intrinsic intestinal denervation in T. cruziinfected mice, due to IFN-␥ -induced NO. In line with this, in vitro neurodegeneration by IFN-␥ -induced NO released from T. cruzi -infected peritoneal macrophages was also reported [64] . Likewise, here we suggest that infiltrating and resident glial cells stimulated by IFN-␥ and S100 ␤ were able to overproduce NO, which contributed to the neurodegenerative process seen in T. cruzi -infected IL-12p40KO spinal cord.…”
Section: Discussionsupporting
confidence: 65%
“…Of note, Arantes et al [63] reported intrinsic intestinal denervation in T. cruziinfected mice, due to IFN-␥ -induced NO. In line with this, in vitro neurodegeneration by IFN-␥ -induced NO released from T. cruzi -infected peritoneal macrophages was also reported [64] . Likewise, here we suggest that infiltrating and resident glial cells stimulated by IFN-␥ and S100 ␤ were able to overproduce NO, which contributed to the neurodegenerative process seen in T. cruzi -infected IL-12p40KO spinal cord.…”
Section: Discussionsupporting
confidence: 65%
“…Our group has studied SCG neurons (Almeida-Leite et al 2007) and glial cells (Almeida-Leite & Arantes 2010) due to their participation in the neuronal degenerative changes induced by T. cruzi . This parasite has a tropism to nervous tissues in intracardiac ganglia (Machado & Ribeiro 1989) and the intramural myenteric plexus, a site where glia parasitism has been reported, whereas neuronal infection is rarely observed (Tafuri 1970, Arantes et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have elucidated crucial roles for glial cells in neuropathological situations through the release of trophic factors, neuroprotective molecules or neurotoxic chemicals that mediate neuronal survival, function, lesion or death (Garden & Moller 2006, Giaume et al 2007). Glial cells are in close contact with neurons in both the central and peripheral nervous systems and are believed to affect them to a greater degree than inflammatory cells and their products (Arantes et al 2000, Almeida-Leite et al 2007, Dewil et al 2007, von Bernhardi 2007). In intestinal Chagas disease, parasitised glial cells and neuronal cells in close proximity to damaged myenteric ganglia is a frequent finding (Tafuri 1970, Arantes et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has a previous experience in obtaining neuronal primary cultures from sympathetic superior cervical ganglion (SCG) of newborn mice (Arantes et al, 2000;Almeida-Leite et al, 2007). These cultures are dependent on Matrigel, an artificial extracellular matrix used in various types of cell cultures (Kleinman et al, 1982(Kleinman et al, , 1987McGuire and Seeds, 1989;Katz et al, 1992;Vukicevic et al, 1992;Mackay et al, 1993).…”
Section: Introductionmentioning
confidence: 99%